THE EFFECT SQ4R TECHNIQUE ON STUDENTS’READING COMPREHENSION - Megawati Megawati; Dini Fitriani (Universitas Singaperbangsa Karawang, 2020)
The research aims to know the effect SQ4R technique on students’ reading comprehension, to know how the implementation SQ4R technique on students’ reading comprehension. The research conducted to the second semester on students English Education program of STKIP Kusuma Negara Jakarta. They are two classes, experiment class and control class. There were 40 students. This research is quantitative method using SPSS 20 software. Experiment class is using SQ4R technique and control class using conventional learning. Instrument reading comprehension was given to experiment class after it class was given by treatment SQ4R technique. The instrument is multiple choice. Then researcher do normality and also homogeinity test. Students’reading comprehension use SQ4R technique get score mean = 85.70; median = 86.50; variance = 20.236, students’ reading comprehension use conventional learning mean = 68.60; median = 69.50; variance = 41.200. There is significant effect (SQ4R) technique on students’ reading comprehension. It can be known that t-score was 16.884 and sig = 0.000 < 0.05. It shown that SQ4R technique give effects to increase students’ ability in reading comprehension.